Dis-entangling the mortgage arrears crisis: The role of the labour market, income volatility and negative equity - McCarthy, Yvonne (Statistical and Social Inquiry Society of Ireland, 2014)
Despite various efforts to address the mortgage arrears crisis, arrears remain at an elevated level. Designing policies to deal with such high levels of distress requires a deep understanding of the precise sources of the problem. Efforts to date, however, have been hampered by a lack of appropriate data. This paper relies on two new and unique datasets which overcome such issues. Specifically, using a combination of administrative loan-level data and a detailed survey of mortgage holders, we assess the role of the labour market, income volatility and negative equity in the mortgage arrears crisis. The results provide new insights on mortgage distress in Ireland; unemployment and negative equity are key drivers, as shown by previous research. However, the results also show that many borrowers experiencing arrears are currently employed. Many of these borrowers have suffered a significant drop in their income, a change in employment conditions or are in fragile employment. This shows that the current mortgage crisis, and efforts to prevent a further deterioration, requires more than simply targeting unemployment. Rather, such efforts should also aim to strengthen overall labour market conditions and job security.
2013-14 Barrington Lecture
Keywords: mortgage arrears; default; debt; negative equity; 314.15